Green synthesis of zinc oxide nanoparticles using different plant extracts and their antibacterial activity against Xanthomonas oryzae pv. oryzae - Solabomi Olaitan Ogunyemi; Yasmine Abdallah; Muchen Zhang; Hatem Fouad; Xianxian Hong; Ezzeldin Ibrahim; Md. Mahidul Islam Masum; Afsana Hossain; Jianchu Mo; Bin Li (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
The synthesis of metal oxide nanoparticles with the use of plant extract is a promising alternative to the conventional chemical method. This work aimed to synthesize zinc oxide nanoparticles (ZnONPs) using plant extract of chamomile flower (Matricaria chamomilla L.), olive leave (Olea europaea) and red tomato fruit (Lycopersicon esculentum M.). The synthesized ZnONPs were characterized by UV–Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM) with EDS profile. The XRD studies confirmed the presence of pure crystalline shapes of ZnO nanoparticles. The ZnONPs synthesized by Olea europaea had the least size range of 40.5 to 124.0 nm as revealed by the SEM observation while XRD revealed a dominant average size of 48.2 nm in the sample which is similar to the size distribution analysis obtained from TEM. The antibacterial effect of ZnONPs synthesized by Olea europaea on Xanthomonas oryzae pv. oryzae (Xoo) strain GZ 0003 had an inhibition zone of 2.2 cm at 16.0 µg/ml which was significantly different from ZnONPs synthesized by Matricaria chamomilla and Lycopersicon esculentum. Also, the bacterial growth, biofilm formation, swimming motility and bacterial cell membrane of Xoo strain GZ 0003 were significantly affected by ZnO nanoparticle. Overall, zinc oxide nanoparticles are promising biocontrol agents that can be used to combat bacterial leaf blight diseases of rice.